2013
DOI: 10.1136/bjophthalmol-2013-303680
|View full text |Cite
|
Sign up to set email alerts
|

Rotation of retinal vascular arcades and comparison with disc-fovea angle in the assessment of cycloposition

Abstract: The rotation of retinal vascular arcades using a first-order approximation technique is no substitute to DFA when assessing torsion in fundus photographs. Of the methods tested, MRA correlated most closely, but DFA remains the gold standard for cycloposition. The rotation of vascular arcades provides a qualitative assessment, particularly in uncertain macular location.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…19,26,27,28 Consistent with the literature, the range of FoDi angles in our patients was -24.4° to +11.6° and the mean value was -6.43±4.96°. The range of absolute deviation angles between the anatomical axis and the horizontal axis was 0-24.4°, and the mean absolute deviation was 7.14±3.95°.…”
Section: Discussionsupporting
confidence: 91%
“…19,26,27,28 Consistent with the literature, the range of FoDi angles in our patients was -24.4° to +11.6° and the mean value was -6.43±4.96°. The range of absolute deviation angles between the anatomical axis and the horizontal axis was 0-24.4°, and the mean absolute deviation was 7.14±3.95°.…”
Section: Discussionsupporting
confidence: 91%
“…The optic disc–fovea angle is another parameter that we used to detect interocular asymmetry. The optic disc–fovea angle measurement is accepted as the gold standard method for assessing the cycloposition [24]. This angle varies widely among normal individuals, but variation between the left and right eyes of the same person was not significant [25].…”
Section: Discussionmentioning
confidence: 99%
“…The authors recommended adjusting BMO-MRW and RNFL thickness for age and sector to optimize the glaucoma diagnosis. It is important to point out that values ranging between À5.6 8 and À7.7 8 have already been reported previously [17][18][19][20]. Using Cirrus OCT, Mwanza et al [21 && ] found an average fovea-to-disc (FoDi) angle of À7.4 8 in 282 multiethnic normal participants (mean age: 47.7 years), 7.1 8 in nonglaucomatous myopes, and 7.6 8 in glaucomatous patients.…”
Section: Optic Nerve Head Parametersmentioning
confidence: 76%